If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 1) + -1 = 3x + 2 Reorder the terms: 3(1 + x) + -1 = 3x + 2 (1 * 3 + x * 3) + -1 = 3x + 2 (3 + 3x) + -1 = 3x + 2 Reorder the terms: 3 + -1 + 3x = 3x + 2 Combine like terms: 3 + -1 = 2 2 + 3x = 3x + 2 Reorder the terms: 2 + 3x = 2 + 3x Add '-2' to each side of the equation. 2 + -2 + 3x = 2 + -2 + 3x Combine like terms: 2 + -2 = 0 0 + 3x = 2 + -2 + 3x 3x = 2 + -2 + 3x Combine like terms: 2 + -2 = 0 3x = 0 + 3x 3x = 3x Add '-3x' to each side of the equation. 3x + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 3x^2-13x=-4 | | x^2+48=0 | | 5(5y-2)-4(4y-3)=y | | 2x(x+6)-10=55 | | 2(2w+8)+2w=76 | | 8y+3y+36=124 | | 4k=16 | | 7(b+3)=4b+2 | | w^2-3w=0 | | 8=4v+13 | | 7(b+3)=13b+2 | | x=3y-27 | | 10x^2+17x+7= | | n+n=20 | | 1.3(X+5)=10 | | 3n+2n=20 | | 6z+28=12z+10 | | 2(x+20)+2x=100 | | x^3+3x^2-x+3=0 | | 2(x+12)+2x=100 | | 6n-6n=-(2+6n)-4(1-n) | | 9xX=70.4 | | 4z=20 | | 3r+2-5(r+1)=6r+4 | | 2(5n+3)-n=3(3n+2) | | 7x+6=18-3x | | 12=14x | | y=3x^2+3 | | x^3-x=-3x^2+3 | | 7x-6=18+3x | | 15y+14=10y+12 | | 4c=8 |